JPOS/JASCC clinical guidelines for delirium in adult cancer patients: a summary of recommendation statements. (26th March 2020) - Matsuda, Yoshinobu; Tanimukai, Hitoshi; Inoue, Shinichiro; Inada, Shuji; Sugano, Koji; Hasuo, Hideaki; Yoshimura, Masafumi; Wada, Saho; Dotani, Chikako; Adachi, Hiroyoshi; Okamoto, Yoshiaki; Takeuchi, Mari; et al.
Abstract: Background: The Japanese Psycho-Oncology Society and Japanese Association of Supportive Care in Cancer recently launched the clinical practice guidelines for delirium in adult cancer patients. The aim of the guidelines was to provide evidence-based recommendations for the clinical assessment and management of delirium in cancer patients. This article reports the process of developing the guideline and summarizes the recommendations made. Methods: The guidelines were developed in accordance with the Medical Information Network Distribution Service creation procedures. The guideline development group, consisting of multidisciplinary members, formulated nine clinical questions. A systematic literature search was conducted to identify relevant articles published prior to through 31 May 2016. Each article was reviewed by two independent reviewers. The level of evidence and the strength of the recommendations were graded using the grading system developed by the Medical Information Network Distribution Service, following the concept of The Grading of Recommendations Assessment, Development and Evaluation system. The modified Delphi method was used to validate the recommendation statements. Results: This article provides a summary of the recommendations with rationales for each, as well as a short summary. Conclusions: These guidelines will support the clinical assessment and management of delirium in cancer patients. However, additional clinical studies are warranted to further improve the management of delirium. Abstract : The Japanese Psycho-Oncology Society and Japanese Association of Supportive Care in Cancer launched the guidelines for delirium. This article reports the process of developing the guideline and summarizes the recommendations.